Performance characteristics of African Cat fish (Clarias gariepinus) fed varying inclusion levels of silk worm pupae (Anaphe infracta) - Olaniyi, CO; Babasanmi, GO (Bangladesh Journal of Animal Science, 2013)
The use of Silkworm (Anaphe infracta) pupae as a protein source was investigated for its ability to replace fishmeal in the diet of Clarias gariepinus, African cat fish. Five dried diets formulated at 40% crude protein were fed to fingerlings of an average initial weight of 14.33g at 0 (control diet), 25, 50, 75 and 100% inclusion levels of silk worm meal. The experiment was conducted for 84 days were measured. Mean weight gain (MWG), specific growth rate (SGR), feed conversion ratio (FCR). The five inclusion levels of silk worm pupae supported the growth of Clarias gariepinus fingerlings, the growth and feed utilization were favoured by high inclusion level of silk worm meal. Significant differences (p<0.05) were observed among the treatments, although there were no significant differences (p>0.05) in the growth parameters between 50% and 75% inclusion levels. The 100% silk worm pupae meal inclusion gave the best final mean weight gain of 10.29g specific growth rate of 0.93%, feed conversion ratio of 2.18 and protein efficiency ratio (PER) of 0.012. The carcass protein and lipid contents increased compared to the levels of both at the beginning of the experiment. Even though, there were no significant differences (p>0.05) among proximate composition of the fish groups fed 25, 50 and 75%. The results showed that diet consists of 100% silk worm meal could be used as a complete replacement for fish meal in the diet formulation for Clarias gariepinus fingerlings. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15787 Bang. J. Anim. Sci. 2013. 42 (1): 76-80